Vascularized bone grafting fixed by biodegradable magnesium screw for treating osteonecrosis of the femoral head. (March 2016) - Zhao, Dewei; Huang, Shibo; Lu, Faqiang; Wang, Benjie; Yang, Lei; Qin, Ling; Yang, Ke; Li, Yangde; Li, Weirong; Wang, Wei; Tian, Simiao; Zhang, Xiuzhi; et al.
Abstract: Hip-preserving surgery with vascularized bone graft implantation has been widely practiced in treating osteonecrosis of the femoral head (ONFH). However, the current approach presents a drawback, in which the implanted bone graft without screw fixation may slip or exhibit a certain degree of displacement postoperatively. This study was designed to investigate the application potential of biodegradable magnesium (Mg) screws for the fixation of vascularized bone graft in ONFH patients. Forty-eight patients were randomly divided into two groups: the Mg screw group (vascularized bone grafting fixed by Mg screws) and the control group (vascularized bone grafting without fixation). During 12 month follow-up period after surgery, treatment outcomes in patients were assessed by multiple imaging techniques including x-ray and computed tomography (CT) scanning as well as functional recovery Harris hip score (HHS). The temporal changes in serum levels of Mg, Ca, and P as well as in vivo degradation rate of Mg screws were determined. The absence of potential adverse effects induced by degradation products from Mg screws on surrounding bone tissue was validated via CT imaging analysis. HHS was significantly improved in the Mg screw group when compared to the control group. X-ray imaging analysis showed that the screw shape did not show significant alteration due to the diameter of Mg screws measured with approximate 25% reduction within 12 months post-surgically. The postoperative serum levels of Ca, Mg, and P, which are relevant for liver and kidney function, were all within normal physiological range in all patients of both groups. The use of biodegradable Mg screws may provide a promising bone graft–screw fixation route in treating ONFH and present considerable potential for orthopedic applications.